THE ANALYSIS OF BIOLOGY STUDENTS’ NEEDS IN ENGLISH LANGUAGE LEARNING - Hermawan Hermawan; Norani Norani (EEAL Journal (English Education and Applied Linguistics Journal), 2022)
This study aims to analyze what English skills are most needed by English students and how to structure the curriculum in English. This research method uses qualitative methods with case study research design. This research was conducted in Biology education at a university in Garut. The subjects of this study were 6 students from level 4 and 25 students from levels 1-4. This study used three instruments, namely interviews, analyzing documents, and questionnaires. The results of the study showed that reading skills that was English skill needed by Biology students, having these abilities could help and support their understanding in reading books, journals, and modules in English. Not only that, speaking skills were also needed by them to support future careers, especially in teaching. Second, mastery of vocabulary and grammar aspects is an aspect that Biology students feel is still lacking, so this has an impact on their speaking and reading processes. Therefore, learning English is still lacking if it is only taught one semester in the Biology Study Program.